Monitoring and Evaluation Practices and Performance of Selected Building Construction Companies in Kiambu County, Kenya - Ndung’u, Samuel N.; Ombati, Robert M.; Gakii, Annstellah K. (Project Management Scientific Journal, 2022)
This study examined the impact of project planning, a key monitoring and evaluation (M&E) practice, on the performance of 168 NCA-registered building construction firms in Kiambu County, Kenya. Applying Systems Theory and a descriptive research design, thestudy utilized multiple linear regression to analyze data from 251 participants. The results identified a significant positive correlation (P = .803, p < 0.001) between project planning and overall performance, noting that while planning often aligns withhigh-level goals, firms frequently struggle to develop specific M&E frameworks. Projects that maintained clear objectives and consistent reviews demonstrated superior cost efficiency and timeliness. Ultimately, the study concludes that systematic planning is essential for success and recommends that firms institutionalize risk assessments and periodic reviews, while advocating for standardized government guidelines to mitigate budget overruns and construction delays.Keywords:Monitoring and Evaluation Practices; Project Performance; Building Construction companies.Citation:Ndung’u, N., S., Ombati, R., &Gakii, A.(2026), “Monitoring and Evaluation Practices and Performance of Selected Building Construction Companies in Kiambu County, Kenya”, Project Management Scientific Journal, 2026, 9(1): pp.21-26
Keywords: Monitoring and Evaluation Practices; Project Performance; Building Construction companies.